On the performance of cooperative vehicular visible light communication networks in curved and rectilinear roadway scenarios - Z??niga, Diego Jeld?? Cuba (2020)
A secure, efficient, robust, and low-cost vehicle-to-vehicle (V2V) communication using the VLC protocol with high transmission rates is a candidate for alleviating high traffic and reducing accidents in dense vehicle environments. Unlike radio frequency (RF) protocols, where communication stability cannot be guaranteed in dense environments, VLC has emerged as a revolutionary alternative. Its applications include road traffic control and accident prevention by exchanging messages between a mix of infrastructure and other vehicles on the road. In this work was studied a V2V-VLC communication between two cars moving along different roadway scenarios: (i) a single three-lane rectilinear carriageway and (ii) a single three-lane curved carriageway. An implementation of full-duplex (FD) cooperative communication protocol has been performed to avoid disruption in the absence of a line-of-sight (LOS) channel and it has been found that the cooperative FD V2V-VLC has promising results for avoiding communication disruptions when cars were traveling in curvilinear roadways. Results in this work can be extended to the case of vehicle-to-infrastructure (V2I) communication scenario, which can also be promising in situations with low-car-density traffic. On another hand, we analyzed a cooperative dual-hop VLC communication which operates with HD and FD protocols in a scenario subject to interference from another vehicle. In particular, we considered four vehicles: source, destination, relay and a possible interferer. The system performance is evaluated considering Bit Error Rate (BER) and other performance metrics. The results show that cooperative communication is an effective solution for scenarios where direct transmission between origin and destination can not be performed. The numerical results are compared for situations with and without interference in order to show the impact in the proposed VLC cooperative scheme.